2021
DOI: 10.1002/term.3271
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin‐11 promotes the mechanical strength of engineered elastic cartilage by enhancing extracellular matrix synthesis and microstructure

Abstract: Limitations of current treatments for auricular cartilage defects have prompted the field of auricular cartilage tissue engineering. To date, inducing the formation of cartilaginous constructs with biochemical and biomechanical properties of native tissue is the final aim. Through hematoxylin-eosin and immunohistochemistry staining, Cadherin-11(CDH11) was confirmed highly expressed in the auricular cartilage tissue and chondrocytes. In vitro, by knockdown and overexpression of CDH11 in chondrocytes, CDH11 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Tese results suggested that CDH11 was involved in chondrogenesis and cartilage ECM synthesis. Tis is consistent with our previous fnding that CDH11 improved the mechanical strength of tissue-engineered elastic cartilage by promoting ECM synthesis and elastic fber assembly [27]. CDH11 has been reported to regulate collagen and elastin synthesis, afecting both the mechanical properties and contractile function of animal tissues such as the aorta, bladder, and skin [28].…”
Section: Discussionsupporting
confidence: 91%
“…Tese results suggested that CDH11 was involved in chondrogenesis and cartilage ECM synthesis. Tis is consistent with our previous fnding that CDH11 improved the mechanical strength of tissue-engineered elastic cartilage by promoting ECM synthesis and elastic fber assembly [27]. CDH11 has been reported to regulate collagen and elastin synthesis, afecting both the mechanical properties and contractile function of animal tissues such as the aorta, bladder, and skin [28].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, upon normalization with the scaffold volume, the contents of collagen in AF, CAF, MAF, and CMAF were approximately 7.7-fold, 8.7-fold, 9.2-fold, and 10.1-fold, respectively, on day 28. These results suggested that scaffolds containing customized millichannels efficiently promoted the secretion of collagen by chondrocytes, which improved the mechanical properties during the formation of cartilage . CMAF possesses good assistance in the development of high-quality cartilage tissue with abundant collagen.…”
Section: Resultsmentioning
confidence: 79%
“…These results suggested that scaffolds containing customized millichannels efficiently promoted the secretion of collagen by chondrocytes, which improved the mechanical properties during the formation of cartilage. 45 CMAF possesses good assistance in the development of high-quality cartilage tissue with abundant collagen.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of the tissue before and after decellularization were measured by indentation testing. As previously described ( Omidi et al, 2014 ; Li et al, 2022 ), the specimens of adipose tissue, dermal tissue, DAM, and ADM were cut into disks with a 6-mm diameter ( n = 5) using a corneal trephine and tested using a 5967 Universal Testing Machine with a 100-N load cell (Instron, Norwood, MA). For unconfined compressive testing, the specimens were compressed at 10 mm/min via the indenters until 100N strain was reached.…”
Section: Methodsmentioning
confidence: 99%